The diagnostic value of soluble urokinase-type plasminogen activator receptor (suPAR) for the discrimination of vertebral osteomyelitis and degenerative diseases of the spine - Scharrenberg, Jan Simon; Brune, Maik (Journal of orthopaedic surgery and research, 2019)
There is still a challenge in discriminating between vertebral osteomyelitis and degenerative diseases of the spine. To this end, we determined the suitability of soluble urokinase-type plasminogen activator receptor (suPAR) and compared the diagnostic potential of suPAR to CRP.